Burden, depression and anxiety in primary caregivers of children and adolescents in renal replacement therapy - Lima,Angélica Godoy Torres (2019)
ABSTRACT Introduction: Chronic kidney disease (CKD) is rare in children, but it causes repercussions in several aspects of life, because the disease and treatment cause great changes in the daily lives of the child and his family, increasing the burden on caregivers. Objective: To evaluate the burden of primary caregivers of children and adolescents who undergo renal replacement therapy (RRT). Methods: Cross-sectional, observational study performed at the Pediatric Renal Unit of a school hospital in the Northeast. Forty-nine primary caregivers of pediatric patients with CKD in RRT followed up in our clinic participated in the study. We used validated instruments to assess burden, depression and anxiety. We ran some tests to analyze the findings of burden, depression and anxiety in the sample. Results: Most of the caregivers are the mothers of these children (89.8%), aged between 36 and 45 years (46.9%), have Elementary School education only (55.1%) and reported feeling pain in the body (69.4%), but they did not have chronic disease. The majority of the children have been in RRT from 1 to 3 years (40.8%), aged from 9 to 11 years (30.6%), are male (55.1%), and under hemodialysis (38.8%). The caregivers had a moderate level of burden (2.10), a high prevalence of moderate to severe depression (18.4%) and anxiety (47%), and a strong correlation between burden, depression and anxiety. Conclusions: Caring for a child with CKD is an intense experience, with negative consequences, due to uncertainties about the future and the very care these children require. We need to do something to help these caregivers better manage care, as well as cope with their own feelings.